Conductive paste and solar battery cell

By controlling the content and particle size of aluminum, silver and copper in the conductive paste, suppressing the interdiffusion and oxidation of silver and aluminum, the problem of increasing the electrode resistance of aluminum content is solved, and high-performance electrode formation of solar cells is achieved.

JP2025019863APending Publication Date: 2025-02-07DOWA ELECTRONICS MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123732
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, although the conductive paste containing aluminum can reduce the contact resistance, the electrode resistance value (line resistance) formed may increase, resulting in an increase in the resistance of the electrode.

Method used

The conductive paste containing silver filler, aluminum and glass melt is used, with an aluminum content of 0.1% to 5.0%, a silver content of 80% to 95%, and a copper content of 0.001% to 5.0%. By controlling the ratio and particle size of copper and silver, the interdiffusion and oxidation of silver and aluminum are suppressed, and the contact resistance and body resistance of the electrode are reduced.

Benefits of technology

The electrode line resistance of the conductive paste containing aluminum is effectively reduced and the performance of solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019863000003
    Figure 2025019863000003
  • Figure 2025019863000001
    Figure 2025019863000001
  • Figure 2025019863000002
    Figure 2025019863000002
Patent Text Reader

Abstract

To provide a conductive paste that can reduce electrode line resistance even when it contains aluminum.SOLUTION: The present invention is a conductive paste including a silver-containing filler, aluminum, a glass frit, and a solvent, and the silver-containing filler includes a first silver powder containing silver and copper, and the aluminum content in the conductive paste is 0.1 mass% or more and 5.0 mass% or less, the silver content is 80 mass% or more and 95 mass% or less, and the copper content is 0.001 mass% or more and 5.0 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive paste and a solar cell. [Background technology]

[0002] Silver powder is used as a bonding material for various electrodes. For example, there are solar cells that have a p-type emitter layer formed by adding a p-type dopant to the surface of an n-type silicon substrate (n-type solar cells), and solar cells that have an n-type emitter layer formed by adding an n-type dopant to the surface of a p-type silicon substrate (p-type solar cells).

[0003] In recent years, the demand for solar cells with high power generation efficiency has been increasing due to the increase in energy demand. In particular, n-type solar cells with a p-type doped front surface have attracted attention because they may have higher cell performance than p-type cells. In this context, when forming an electrode by applying a conductive paste to a semiconductor layer (the above-mentioned p-type emitter layer or p-type substrate) that has been made p-type by a p-type dopant, an attempt has been made to improve the performance of solar cells by making the conductive paste contain an element that becomes a p-type impurity for the silicon substrate.

[0004] For example, Patent Document 1 discloses that a silver-aluminum paste containing a combination of silver and aluminum as a conductive filler is used to form electrodes in order to provide a solar cell with improved electrical properties such as favorable contact resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2016-519839 Summary of the Invention [Problem to be solved by the invention]

[0006] However, as in Patent Document 1, when aluminum is contained in the conductive paste, the contact resistance (interface resistance) can be reduced, but the resistance value (line resistance value) of the formed electrode may increase. Therefore, it is desired to reduce the resistance value (line resistance value) of the formed electrode in the conductive paste containing aluminum.

[0007] Therefore, an object of the present invention is to provide a conductive paste that can reduce the line resistance of an electrode even if it contains aluminum. Another object of the present invention is to provide a solar cell having excellent performance. [Means for solving the problem]

[0008] As a result of extensive research by the inventors to solve the above-mentioned problems, the inventors have completed the present invention described below.

[0009] That is, the gist of the present invention for solving the above-mentioned problems is as follows.

[0010] [1] A conductive paste comprising a silver-containing filler, aluminum, a glass frit, and a solvent, The silver-containing filler comprises silver powder containing silver and copper, The conductive paste has an aluminum content of 0.1% by mass or more and 5.0% by mass or less, a silver content of 80% by mass or more and 95% by mass or less, and a copper content of 0.001% by mass or more and 5.0% by mass or less.

[0011] [2] The conductive paste according to [1], wherein the copper content in the conductive paste is 0.6% by mass or more and 5.0% by mass or less.

[0012] [3] The conductive paste according to [1] or [2], wherein the copper content in the conductive paste is 1.5% by mass or more and 5.0% by mass or less.

[0013] [4] The conductive paste according to any one of [1] to [3], wherein the silver-containing filler further contains second silver powder made of silver.

[0014] [5] The conductive paste according to any one of [1] to [4], wherein the first silver powder has a copper content of 1.1 mass % or more.

[0015] [6] The conductive paste according to any one of [1] to [5], wherein the first silver powder has a copper content of 5.0 mass % or more.

[0016] [7] The conductive paste according to any one of [1] to [6], wherein the first silver powder has an average diameter of 0.3 μm or more and 3.0 μm or less.

[0017] [8] The conductive paste according to any one of [1] to [7], wherein the aluminum is aluminum powder.

[0018] [9] The conductive paste according to any one of [1] to [8], which is used for forming an electrode provided in an n-type solar cell.

[0019]

[10] A solar cell comprising an electrode formed using the conductive paste according to any one of [1] to [8]. Effect of the Invention

[0020] According to the present invention, it is possible to provide a conductive paste that can reduce the line resistance of an electrode even if it contains aluminum. Moreover, according to the present invention, a solar cell having excellent performance can be provided. [Brief description of the drawings]

[0021] [Figure 1] 1 is a scanning electron microscope photograph of a silver-copper alloy powder serving as the first silver powder used in Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] (Terminology and Measurement Methods) Prior to describing the embodiments, the terms and measurement methods used in this specification will be described.

[0023] <Measurement of copper and aluminum contents in conductive paste> The amounts of copper and aluminum in the conductive paste were determined by the following analytical method. 1) 1 g of the paste was precisely weighed, washed with acetone, and then dried to obtain a sample. 2) After drying, 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added to the sample, and the sample was heated at 200°C for 30 minutes. 3) Pure water was added to the heated solution in 2) to make the volume 100 mL, and 5 mL was taken from that and pure water was added again to make the volume 100 mL to prepare a sample for ICP analysis. 4) The copper and aluminum standard solutions used to create the calibration curves were prepared by adjusting the silver concentration using 5N silver to the same level as the samples for ICP analysis. 5) ICP volumetric analysis was performed using an Agilent 5800 ICP-ES (Agilent Technologies).

[0024] <Measurement of silver content in conductive paste> The amount of silver in the conductive paste was determined by the following analytical method. 1) 1 g of the paste was precisely weighed, washed with acetone, and then dried to obtain a sample. 2) After drying, 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added to the sample, and the sample was heated at 200°C for 30 minutes. 3) The solution after heating in 2) was allowed to cool, and 15 mL of pure water and 10 mL of hydrochloric acid (for precision analysis) were added, followed by heating at 150°C for 30 minutes. 4) The resulting silver chloride was allowed to age for more than 12 hours. 5) The silver chloride was filtered through a precisely weighed glass filter and washed with pure water. 6) The glass filter containing silver chloride was dried in a dryer at 120°C for approximately 3 hours until it reached a constant weight. 7) After cooling in the desiccator for at least 1 hour, the glass filter containing silver chloride was precisely weighed and the silver content was calculated from the mass of silver chloride produced.

[0025] <Measurement of Copper Content in the First Silver Powder> The method for quantifying copper in the first silver powder was carried out by the following analytical method. 1) Weigh accurately 1 g of the sample, add 15 mL of pure water and 10 mL of nitric acid (for precise analysis), and heat at 200 °C for 30 minutes. 2) Add pure water to the solution after heating in 1) to make the volume constant at 100 mL, take 5 mL from it, add pure water again to make the volume constant at 100 mL, thus preparing a sample for ICP analysis. 3) Standard solutions of copper and aluminum used for preparing the calibration curve were prepared by adjusting with 5N silver to have the same silver concentration as the sample for ICP analysis. 4) ICP volume constant was carried out using Agilent 5800 ICP - ES manufactured by Agilent Technologies.

[0026] <Average Diameter (SEM Average Diameter)> The average diameter (SEM average diameter) was measured as the average value of the Heywood diameters for 100 or more particles whose outer shapes could be fully recognized in an SEM image with a magnification of 5,000 times using image - processing software Mac - View (Ver.4) manufactured by MOUNTECH.

[0027] <BET Specific Surface Area> In this specification, the "BET specific surface area" was measured by the BET one - point method by nitrogen adsorption using Macsorb HM - model 1210 (manufactured by MOUNTECH). In the measurement of the BET specific surface area, the degassing conditions before measurement were 60 °C for 10 minutes.

[0028] <Particle Size Distribution> In this specification, the cumulative 50% particle diameter (D 50 ) of the silver powder based on volume was measured by a laser diffraction / scattering particle size distribution measuring device (manufactured by Microtrac Bell Corporation, Microtrac MT - 3300 EXII).

[0029] (Conductive Paste) The conductive paste of the present invention contains a silver-containing filler, aluminum, a glass frit, and a solvent, and may further contain components other than the silver-containing filler, aluminum, the glass frit, and the solvent (hereinafter, these may be referred to as "other components"). In the conductive paste of the present invention, the silver-containing filler contains silver powder containing silver and copper. Furthermore, the conductive paste of the present invention has an aluminum content of 0.1% by mass or more and 5.0% by mass or less, a silver content of 80% by mass or more and 95% by mass or less, and a copper content of 0.001% by mass or more and 5.0% by mass or less. The conductive paste as described above can reduce the line resistance of the electrode even if it contains aluminum. The reason for this is that, while it is presumed that the use of aluminum increases the bulk resistance of the electrode, which may result in an increase in the line resistance of the electrode, by setting the aluminum, silver and copper contents in the conductive paste within respective predetermined ranges, it is presumed that the formation of intermetallic compounds due to interdiffusion of silver and aluminum and the oxidation of the aluminum surface can be effectively suppressed, and as a result, the contact resistance and bulk resistance of the electrode can be effectively reduced.

[0030] The aluminum content in the conductive paste means the mass ratio of aluminum to the total mass of all components in the conductive paste. The aluminum content in the conductive paste is 0.1 mass% or more, preferably 0.5 mass% or more, more preferably 1 mass% or more, and 5.0 mass% or less, preferably 3.0 mass% or less, more preferably 2.0 mass% or less. If the aluminum content in the conductive paste is 0.1 mass % or more, the contact resistance of the electrodes can be effectively reduced. On the other hand, if the aluminum content in the conductive paste is 5.0 mass % or less, an increase in the bulk resistance of the electrode can be effectively suppressed.

[0031] The silver content in the conductive paste means the mass ratio of silver to the total mass of all components in the conductive paste. The silver content in the conductive paste is 80 mass% or more, preferably 81 mass% or more, more preferably 82 mass% or more, and 95 mass% or less, preferably 90 mass% or less, more preferably 85 mass% or less, and even more preferably 84 mass% or less. If the silver content in the conductive paste is within the above range, the line resistance of the electrodes can be effectively reduced.

[0032] The copper content in the conductive paste means the mass ratio of copper to the total mass of all components in the conductive paste. The copper content in the conductive paste is 0.001 mass% or more, preferably 0.5 mass% or more, more preferably 0.6 mass% or more, even more preferably 1.0 mass% or more, even more preferably 1.5 mass% or more, and is 5.0 mass% or less, preferably 4.0 mass% or less, and more preferably 3.0 mass% or less. If the copper content in the conductive paste is 0.001 mass % or more, the bulk resistance of the electrode can be effectively reduced. On the other hand, if the copper content in the conductive paste is 5.0 mass % or less, the risk of copper diffusing into materials (eg, silicon) that can be used for the substrate of a solar cell can be effectively reduced.

[0033] <Silver-containing filler> The silver-containing filler contains at least a first silver powder, which will be described later, and may further contain a second silver powder, which will be described later and is made of silver.

[0034] The copper content in the silver-containing filler means the mass ratio of copper to the total mass of silver and copper in the silver-containing filler. The copper content in the silver-containing filler is 0.001 mass% or more, preferably 0.1 mass% or more, more preferably 0.6 mass% or more, even more preferably 1 mass% or more, even more preferably 1.5 mass% or more, preferably 5.0 mass% or less, more preferably 4.0 mass% or less, even more preferably 3.0 mass% or less. The copper in the conductive paste is preferably contained as copper possessed by the first silver powder contained in the silver-containing filler.

[0035] The content of the silver-containing filler in the conductive paste means the mass ratio of the silver-containing filler to the total mass of all components in the conductive paste. The content of the silver-containing filler in the conductive paste is not particularly limited as long as the aluminum content, silver content, and copper content in the conductive paste are within the specified range, and may be, for example, 80 mass% or more, for example, 98 mass% or less, or 95 mass% or less.

[0036] [First silver powder] The first silver powder is a silver powder containing silver and copper. Here, the first silver powder is not particularly limited as long as it contains silver and copper, but examples thereof include silver and copper alloy powder, copper-attached silver powder, and silver-coated copper powder. As long as the first silver powder contains silver and copper as main components, it may have a surface treatment agent on the surface, may contain impurities or oxygen due to the manufacturing process, and may be partially oxidized copper. The component contained most abundantly in the first silver powder is silver, and the component contained next most abundantly is copper.

[0037] The amount of impurities other than silver and copper in the first silver powder is preferably less than 10.0 mass%, more preferably 5.0 mass% or less, even more preferably 1.0 mass% or less, and even more preferably 0.001 mass% or less, i.e., it is even more preferable that the first silver powder consists of silver and copper.

[0038] The silver content in the first silver powder means the mass ratio of silver to the total mass of silver and copper in the first silver powder, and is usually more than 50 mass%. The silver content in the first silver powder is preferably 60% by mass or more, more preferably 70% by mass or more, and is preferably 98.9% by mass or less, more preferably 98.5% by mass or less, even more preferably 90% by mass or less, and even more preferably 80% by mass or less. When the silver content in the first silver powder is within the above range, the line resistance of the electrode can be effectively reduced, and the increase in the cost of the conductive paste due to the use of silver can be effectively suppressed.

[0039] The copper content in the first silver powder means the mass ratio of copper to the total mass of silver and copper in the first silver powder, and is usually less than 50 mass %. The copper content in the first silver powder is preferably 0.001% by mass or more, more preferably 1.1% by mass or more, even more preferably 5.0% by mass or more, even more preferably 20% by mass or more, and is preferably 40% by mass or less, and more preferably 30% by mass or less. When the copper content in the first silver powder is 0.001% by mass or more, the bulk resistance of the electrode can be effectively reduced. On the other hand, if the copper content in the first silver powder is 40 mass % or less, the risk of copper diffusing into materials (eg, silicon) that can be used for the substrate of a solar cell can be effectively reduced.

[0040] The average diameter (SEM average diameter) of the first silver powder is preferably 0.3 μm or more, and is preferably 3.0 μm or less, and more preferably 2.0 μm or less. When the average diameter (SEM average diameter) of the first silver powder is 0.3 μm or more, an increase in the viscosity of the conductive paste can be effectively suppressed, and as a result, when the conductive paste is ejected, etc. to print an electrode, printing defects can be suppressed, and the risk of breakage of the formed electrode can be effectively suppressed. On the other hand, the electrodes of solar cells are rapidly becoming thinner in order to increase the amount of light received and reduce the amount of materials used. If the average diameter (SEM average diameter) of the first silver powder is 3.0 μm or less, the conductive paste can be suitably used to form thin electrodes.

[0041] The BET specific surface area of ​​silver powder is 0.1m 2 / g or more, and 0.3m 2 / g or more is more preferable, and 0.45m 2 / g or more is more preferable, 2 / g or less, and 0.8m 2 It is more preferable that the molecular weight is not more than 1 / g. When the BET specific surface area of ​​the first silver powder is within the above range, the line resistance of the electrode can be effectively reduced.

[0042] Cumulative 50% particle size of the first silver powder (D 50 ) is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 1.5 μm or more, and is preferably 6 μm or less, and more preferably 2.5 μm or less. D 50 If is within the above range, the line resistance of the electrode can be effectively reduced.

[0043] The content of the first silver powder in the silver-containing filler means the mass ratio of the first silver powder to the total mass of the silver-containing filler. The content of the first silver powder in the silver-containing filler is not particularly limited as long as the silver content and copper content in the conductive paste are within the specified ranges, and may be, for example, 0.1 mass% or more, 1.5 mass% or more, 3 mass% or more, or 5 mass% or more.

[0044] Examples of the above-mentioned first silver powder include silver and copper alloy powder, copper-adhered silver powder, silver-coated copper powder, etc., and are not particularly limited. For example, atomized silver-copper powder produced by an atomization method manufactured by DOWA Electronics Co., Ltd. can be used.

[0045] [Secric silver powder] The second silver powder that may be optionally contained in the silver-containing filler is a silver powder made of silver, and preferably has a copper content of less than 0.001% by mass, and is clearly distinguished from the first silver powder containing copper. Here, the second silver powder may be in various shapes such as spherical, flake, sheet, block, etc., so long as it is a silver powder, but is preferably a spherical silver powder from the viewpoint of being suitable for use in forming a thin-line electrode from the conductive paste.

[0046] The average diameter (SEM average diameter) of the second silver powder is preferably 3.0 μm or less, and more preferably 2.0 μm or less. Solar cell electrodes are rapidly becoming thinner in order to increase the amount of light received and reduce the amount of materials used. If the average diameter (SEM average diameter) of the silver powder is 3.0 μm or less, the conductive paste can be suitably used to form thin electrodes. On the other hand, the average diameter (SEM average diameter) of the second silver powder is, for example, 0.3 μm or more.

[0047] The BET specific surface area of ​​silver powder is 0.1m 2 / g or more, and 0.3m 2 / g or more is more preferable, and 1m 2 / g or less, and 0.8m 2 / g or less is more preferable, and 0.5m 2 It is more preferable that the molecular weight is not more than 1 / g. If the BET specific surface area of ​​the second silver powder is within the above range, the line resistance of the electrode can be effectively reduced.

[0048] Cumulative 50% particle size of silver powder by volume (D 50 ) is preferably 0.5 μm or more, more preferably 1 μm or more, and is preferably 6 μm or less, more preferably 2.5 μm or less, and even more preferably 1.9 μm or less. D 50 If is within the above range, the line resistance of the electrode can be effectively reduced.

[0049] The content of the second silver powder in the silver-containing filler means the mass ratio of the second silver powder to the total mass of the silver-containing filler. The content of the second silver powder in the silver-containing filler is not particularly limited as long as the silver content and copper content in the conductive paste are within the predetermined ranges.

[0050] The second silver powder mentioned above is not particularly limited, but may be silver powder produced by a wet reduction method or silver powder produced by an atomization method, and an example of a spherical silver powder produced by a wet reduction method is "AG-4-8FD" manufactured by DOWA Electronics Co., Ltd.

[0051] <Aluminum> The aluminum contained in the conductive paste of the present invention may be either metallic aluminum or an aluminum compound, but is preferably metallic aluminum. Examples of the form of metallic aluminum include aluminum (metallic aluminum) and an aluminum alloy. The aluminum is preferably in the form of a powder, and examples of the powder include aluminum powder made of metallic aluminum, aluminum alloy powder, silver-coated aluminum powder, aluminum-adhered silver powder, etc. As the aluminum, it is particularly preferable to use aluminum powder. When the aluminum powder is a powder made of metallic aluminum, it usually does not contain any components other than impurities (e.g., iron, silicon, etc.) that are inevitably mixed in during production. The content of metallic aluminum in the aluminum powder is usually 99 mass% or more, preferably 99.5 mass% or more, and more preferably 99.8 mass% or more. The surfaces of the aluminum powder, aluminum alloy powder, silver-coated aluminum powder, aluminum-adhered silver powder, etc. may be oxidized. For example, the aluminum powder may have an aluminum oxide film on the surface.

[0052] When the aluminum is in the form of powder, the average diameter (SEM average diameter) of the powder is preferably 3.0 μm or less, and more preferably 2.0 μm or less. If the average diameter (SEM average diameter) of the powdered aluminum is 3.0 μm or less, the conductive paste can be suitably used for forming thin electrodes.

[0053] The aluminum content in the conductive paste means the mass ratio of aluminum to the total mass of all components in the conductive paste. The aluminum content in the conductive paste is not particularly limited as long as the aluminum content, silver content, and copper content in the conductive paste are within a predetermined range, and is, for example, 0.1 mass% or more, 0.5 mass% or more, or 1 mass% or more, for example, 5 mass% or less, 3 mass% or less, or 2 mass% or less.

[0054] <Glass frit> The glass frit is a component that can improve the adhesion between the obtained electrode and the substrate when the conductive paste is sintered. The glass frit can be appropriately selected according to the purpose, and can be used without any particular limitation as long as it is generally usable for solar cells, but it is preferable that it contains components such as Si, B, Al, Bi, Li, Na, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, and Cr. Such components can be present in the glass frit in the form of oxides, compounds that generate oxides when heated, other compounds, and mixtures thereof. Here, preferred oxides are alkali metal oxides, alkaline earth metal oxides, rare earth oxides, Group 14 to Group 16 oxides, other oxides, or combinations thereof. The glass frit is usually in the form of glass powder.

[0055] The content of the glass frit in the conductive paste means the mass ratio of the glass frit to the total mass of all components in the conductive paste. The content of the glass frit in the conductive paste is preferably 0.1 mass% or more and 10 mass% or less.

[0056] <Solvent> The solvent (i.e., dispersion medium) is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include texanol, butyl carbitol acetate, tributyl citrate, 1-octanol, terpineol, butyl carbitol, etc. These may be used alone or in combination of two or more.

[0057] The content of the solvent in the conductive paste means the mass ratio of the solvent to the total mass of all components in the conductive paste. The content of the solvent in the conductive paste is preferably 1 mass% or more and 19 mass% or less.

[0058] <Other ingredients> Other components that may be optionally contained in the conductive paste include, for example, a binder, a dispersant, a viscosity modifier, etc. These may be used alone or in combination of two or more kinds.

[0059] Examples of the binder include epoxy resins, acrylic resins, polyester resins, polyimide resins, polyurethane resins, phenoxy resins, silicone resins, cellulose, etc. These may be used alone or in combination of two or more.

[0060] Examples of dispersants include behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, ricinoleic acid, oleic acid, linoleic acid, linolenic acid, benzotriazole, triacetin, etc. These may be used alone or in combination of two or more.

[0061] Examples of the viscosity modifier include methylphenylpolysiloxane, hydrogenated castor oil, and fatty acid amides.

[0062] <Conductive paste properties> The viscosity of the conductive paste is not particularly limited and can be selected appropriately depending on the purpose, but under conditions of a paste temperature of 25°C and a rotation speed of 1 rpm, it is preferably 150 Pa·s or more, more preferably 200 Pa·s or more, and is preferably 800 Pa·s or less, and more preferably 750 Pa·s or less. If the viscosity of the conductive paste is 150 Pa·s or more, printing defects such as "bleeding" and "printing sagging" that can occur when forming a conductive film by printing or other methods can be effectively suppressed. On the other hand, if the viscosity of the conductive paste is 800 Pa·s or less, breakage in the resulting conductive film can be effectively prevented, making it possible to form a thinner conductive film.

[0063] <Applications of conductive paste> The conductive paste of the present invention can be used to form electrodes. In addition, the conductive paste of the present invention is preferably used to form electrodes for n-type solar cells, since aluminum acts as a p-type impurity for a silicon substrate and can improve the performance of the n-type solar cell.

[0064] <Method of manufacturing conductive paste> The method for producing the conductive paste of the present invention is not particularly limited, and for example, the conductive paste can be obtained by mixing each material that can be contained in the conductive paste described above, and dispersing and / or kneading the resulting mixture. For dispersion and kneading, for example, ultrasonic dispersion, a disperser, a three-roll mill, a ball mill, a bead mill, a two-axis kneader, a self-revolving mixer, etc. can be used.

[0065] (Solar cell) The solar cell of the present invention includes electrodes formed using the conductive paste of the present invention described above. The solar cell of the present invention has excellent performance because it includes electrodes formed using the conductive paste of the present invention described above. The electrodes included in the solar cell of the present invention are usually films formed by applying or printing the above-mentioned conductive paste of the present invention onto a substrate or the like, and then firing the same.

[0066] The solar cell of the present invention is not particularly limited as long as it has an electrode formed using the conductive paste of the present invention, and may appropriately have a semiconductor substrate, a diffusion layer, an anti-reflective layer, a BSF (Back Surface Field) layer, a front electrode, a back electrode, etc. EXAMPLES

[0067] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way. The average diameter (SEM average diameter), the BET specific surface area, the copper content in the first silver powder, the copper content and aluminum content in the conductive paste, and the silver content in the conductive paste were measured by the methods described above. The particle size distribution and line resistance were measured by the following procedure.

[0068] [Measurement of particle size distribution] Cumulative 50% particle size by volume (D 50 ) was measured by the following method. 0.1 g of the sample was added to 40 mL of isopropyl alcohol (IPA) and dispersed for 2 minutes using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho Co., Ltd.; 19.5 kHz, tip diameter 18 mm), and then the particle size distribution was measured using a laser diffraction / scattering type particle size distribution analyzer (Microtrac MT-3300 EXII, manufactured by Microtrack Bell Corporation).

[0069] [Measurement of line resistance] Measurement terminals were placed on both ends of the printed electrodes of the electrode-attached substrates obtained in the Examples and Comparative Examples, and the resistance value (line resistance value) of the electrodes was measured with a digital multimeter (manufactured by ADC Corporation).

[0070] Example 1 <Preparation of conductive paste> The first silver powder was a silver-copper alloy powder (manufactured by DOWA Electronics Co., Ltd., SEM average diameter: 1.2 μm, cumulative 50% particle diameter: 2.0 μm, BET specific surface area: 0.68 m) with a silver content of 72 mass% and a copper content of 28 mass%, produced by an atomization method. 2 / g), and silver powder consisting of silver as the second silver powder (manufactured by DOWA Electronics, "AG-4-8FD", SEM average diameter: 1.4 μm, cumulative 50% particle diameter: 1.8 μm, BET specific surface area: 0.44 m 2 The following materials were mixed to obtain a mixture having the composition shown in Table 1: aluminum powder (SEM average diameter: 2.0 μm) with a metallic aluminum content of 99.87 mass% and an impurity content of 0.13 mass% (iron 0.09 mass% and silicon 0.04 mass%) as aluminum; glass powder (containing PbO as the main component, and containing B2O3, SiO2 and other oxides) as glass frit; ethyl cellulose, texanol, butyl carbitol acetate, tributyl citrate, 1-octanol, oleic acid, triacetin, methylphenylpolysiloxane, hydrogenated castor oil, and fatty acid amide. Next, the obtained mixture was premixed under conditions of a planetary centrifugal mixer (revolution 1000 rpm) and then kneaded with a three-roll mill (manufactured by Esact) to obtain a conductive paste. As shown in Table 2, the silver content in the conductive paste is 83.06 mass%, the copper content is 2.39 mass%, and the aluminum content is 1.22 mass%, the silver-containing filler content in the conductive paste is 85.45 mass%, and the copper content in the silver-containing filler is 2.80 mass%. FIG. 1 shows a scanning electron microscope photograph (2,000 times) of the silver-copper alloy powder as the first silver powder.

[0071] <Electrode formation> The conductive paste obtained above was used to fabricate a silicon substrate with a thickness of about 170 μm (for solar cells, texture formation, SiN xA straight line shape was printed by screen printing on the wafer (on which a film had already been formed). The straight line had a designed line width of 12 μm and a length of 150 mm. A Microtec printer was used for printing, and printing was performed at a ski speed of 350 mm / s. After printing, the wafer was dried for 5 minutes in a dryer set at a temperature of 200°C, and then baked in a solar cell baking furnace (manufactured by NGK) under conditions such that the peak temperature of the wafer's upper surface was 750°C, producing a substrate with electrodes. The line resistance value was measured using the obtained substrate with electrodes. The results are shown in Table 2.

[0072] (Examples 2 and 3, Comparative Example 1) Various operations and measurements were carried out in the same manner as in Example 1, except that the composition of the conductive paste was changed as shown in Table 1. The results are shown in Table 2.

[0073] [Table 1]

[0074] [Table 2]

[0075] As is clear from Table 2, the conductive pastes of the examples are capable of reducing the line resistance of the electrodes. [Industrial Applicability]

[0076] An object of the present invention is to provide a conductive paste that can reduce the line resistance of an electrode even when it contains aluminum. Moreover, according to the present invention, a solar cell having excellent performance can be provided.

Claims

1. A conductive paste comprising a silver-containing filler, aluminum, a glass frit, and a solvent, The silver-containing filler comprises silver powder containing silver and copper, The conductive paste has an aluminum content of 0.1% by mass or more and 5.0% by mass or less, a silver content of 80% by mass or more and 95% by mass or less, and a copper content of 0.001% by mass or more and 5.0% by mass or less.

2. The conductive paste according to claim 1 , wherein the copper content in the conductive paste is 0.6% by mass or more and 5.0% by mass or less.

3. The conductive paste according to claim 1 , wherein the copper content in the conductive paste is 1.5% by mass or more and 5.0% by mass or less.

4. The conductive paste of claim 1 , wherein the silver-containing filler further comprises a second silver powder made of silver.

5. The conductive paste according to claim 1 , wherein the copper content in the first silver powder is 1.1% by mass or more.

6. The conductive paste according to claim 1 , wherein the copper content in the first silver powder is 5.0 mass % or more.

7. The conductive paste according to claim 1 , wherein the first silver powder has an average particle size of 0.3 μm or more and 3.0 μm or less.

8. The conductive paste of claim 1 , wherein the aluminum is aluminum powder.

9. The conductive paste according to any one of claims 1 to 8, which is used for forming an electrode provided in an n-type solar cell.

10. A solar cell comprising an electrode formed using the conductive paste according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Particles containing al and ag in conductive pastes and solar cell formulations

    JP2016519839A